After such kindness - Arnold, Gaynor, author (London : Tandal Street Pr., 2013)
When the writer, Oxford scholar and photographer John Jameson visits the home of his vicar friend, he is entranced by Daisy, his youngest daughter. Jameson charms her with his wit and child-like imagination, teasing her with riddles and inventing humorous stories as they enjoy afternoons alone by the river and in his rooms. The shocking impact of this unusual friendship is only brought to light when, years later, Daisy, unsettled in her marriage, rediscovers her childhood diaries hidden in an old toy chest. Inspired by the tender and troubling friendship between Lewis Carroll and Alice Liddell, After Such Kindness demonstrates Gaynor Arnold's extraordinary 'capacity to imagine the truth behind the facts'. With the same assured feel for the Victorian period displayed in her prize-listed debut, Arnold brings to scintillating life an idiosyncratic genius and his timeless muse.